JIHAD IN THE NAME OF GOD; AN EXAMINATION OF THE WORLD'S RELIGIOUS FUNDAMENTALISM AND RADICALISM MOVEMENTS - Hilmi Ridho; Afif Sabil (university Of islam, 2023)
The discourse of terrorism, extremism, and fundamentalism movements is not a new issue, but what becomes a public question is why all these actions are always in the name of religion. From various events, the majority of people claim the action was carried out by hardline groups with the face of Islam, such as Al-Qaeda, ISIS, Boko Haram, Abu Sayyaf, and so on. In fact, acts of terror are also carried out by groups with other religious backgrounds, such as the bombings that occurred in Malegaon, Maharashtra, and in Modasa, Gujarat in India on September 29, 2008. The question is, is it true that religions teach their followers to commit violence and justify such acts? What are the factors behind the emergence of religious violence? This research aims to examine religious sects from all religions in the world that often commit violence in the name of religion. In addition, it also wants to know the history of the emergence and movement of fundamentalist sects that become a forum for religious radicalism.